2001
DOI: 10.1063/1.1368180
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of buckling of a compressed film on a viscous substrate

Abstract: Compressively-stressed elastic films on finite-thickness viscous substrates can undergo a buckling instability that relieves stresses but destroys the planarity of the film. A linear-stability analysis is performed to determine the onset and maximally unstable mode of this buckling instability as a function of misfit strain, viscous layer thickness, and viscosity. We find that the onset of the buckling instability of the film on a glass layer is the same as that for a compressively stressed free-standing film.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 6 publications
3
74
0
Order By: Relevance
“…A similar result for the vertical stress exerted by a finite, viscous matrix on the layer boundary was recently presented by Sridhar et al [2001] but for free slip conditions (t xz = 0 at layer-matrix boundary). Sridhar et al [2001] investigated buckling of an elastic layer resting on a finite, viscous matrix without the effects of gravity. Equations (30) and (31) are substituted into (1), and the resulting nondimensional amplification rate for folding of a ductile layer resting on a finite, viscous matrix under the effects of gravity is…”
Section: Folding Of a Ductile Layer Resting On Ansupporting
confidence: 48%
See 3 more Smart Citations
“…A similar result for the vertical stress exerted by a finite, viscous matrix on the layer boundary was recently presented by Sridhar et al [2001] but for free slip conditions (t xz = 0 at layer-matrix boundary). Sridhar et al [2001] investigated buckling of an elastic layer resting on a finite, viscous matrix without the effects of gravity. Equations (30) and (31) are substituted into (1), and the resulting nondimensional amplification rate for folding of a ductile layer resting on a finite, viscous matrix under the effects of gravity is…”
Section: Folding Of a Ductile Layer Resting On Ansupporting
confidence: 48%
“…Results obtained with our analytical theory compare well with analytical and analogue results obtained by Ramberg [1963] for folding, while the matrix above and below the layer has the same finite thickness and gravity can be ignored. Sridhar et al [2001] showed that for folding of an elastic layer resting on a finite, viscous matrix, both the dominant wavelength and the maximal amplification rate decrease with decreasing matrix thickness. Therefore the matrix thickness has the same influence on the dominant wavelength and the maximal amplification rate, independent of layer rheology for both free slip and no slip between layer and matrix.…”
Section: Folding Of a Ductile Layer Resting On Anmentioning
confidence: 99%
See 2 more Smart Citations
“…To describe the salient features of the wrinkle dynamics, here we give a simplified analysis, assuming that the BPSG layer is so thick that its thickness does not enter into the consideration. The analysis follows those in [28,40]. More comprehensive analyses are given in [29,-~31].…”
Section: Growing Wrinklesmentioning
confidence: 98%